MAJAS HIPERBOLA PADA CERPEN KARYA SISWA KELAS 7 SMP NEGERI 3 PANGGUL TRENGGALEK JAWA TIMUR - Aulia Nova Ardana Putri; Suyatno Suyatno (Universitas Batanghari, 2026)
This research aims to describe the forms, meanings, and functions of hyperbolic figures of speech in short stories written by 7th-grade students of SMP Negeri 3 Panggul. By applying a qualitative descriptive method through a stylistic approach, this study selected 6 out of 29 student short stories, yielding 10 data points analyzed using the stylistic theories of Rachmat Djoko Pradopo and Burhan Nurgiyantoro. The findings reveal that students utilize five categories of hyperbole: quality, quantity, time, size, and emotion. The use of these hyperboles demonstrates the students' proficiency as novice writers in spontaneously expressing feelings while enhancing the linguistic aesthetics of their literary works. It is expected that the results of this study will contribute as supplementary teaching material in literary studies and serve as a reference for future research focusing on stylistic analysis of works by adolescent writers.